2014
DOI: 10.1111/apha.12360
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of glucose control: roles for glucose‐sensing neurones

Abstract: The brain can be viewed as a sophisticated control module for stabilizing blood glucose. A review of classical behavioural evidence indicates that central circuits add predictive (feedforward/anticipatory) control to the reactive (feedback/compensatory) control by peripheral organs. The brain/cephalic control is constructed and engaged, via associative learning, by sensory cues predicting energy intake or expenditure (e.g. sight, smell, taste, sound). This allows rapidly measurable sensory information (rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 103 publications
(151 reference statements)
0
24
0
Order By: Relevance
“…In addition, when optical stimulation of LH-MCH is combined with consumption of the non-caloric sweetener sucralose, MCH neuronal activation can substitute for glucose metabolism, reversing the normal preference for sucrose over sucralose and resulting in evoked dopamine responses in the striatum [51]. These findings suggest that MCH neurons form part of a complex network that integrates sensory, reward, and nutritional information from the periphery and central nervous system [51,52]. Based on this multifaceted role in the control of food intake, MCH neurons may function within a framework of allostasis [53], in which, through learning, animals come to anticipate their needs rather than simply reacting to them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, when optical stimulation of LH-MCH is combined with consumption of the non-caloric sweetener sucralose, MCH neuronal activation can substitute for glucose metabolism, reversing the normal preference for sucrose over sucralose and resulting in evoked dopamine responses in the striatum [51]. These findings suggest that MCH neurons form part of a complex network that integrates sensory, reward, and nutritional information from the periphery and central nervous system [51,52]. Based on this multifaceted role in the control of food intake, MCH neurons may function within a framework of allostasis [53], in which, through learning, animals come to anticipate their needs rather than simply reacting to them.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this multifaceted role in the control of food intake, MCH neurons may function within a framework of allostasis [53], in which, through learning, animals come to anticipate their needs rather than simply reacting to them. For example, MCH may respond to sucrose-associated CSs leading to the release of insulin [48,49,52] in anticipation of glucose consumption, enhancing the efficiency of glucose metabolism [53]. It is tempting to speculate, however, that this efficient design for predictive regulation [52,53] may also lead to vulnerabilities to other mechanisms of learning that influence food intake such as CPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory dysfunction in narcolepsy has been reported to be reversed by intranasal orexin A (hypocretin 1) [63]. Animal studies have observed that orexin neurons are glucose-sensing, being inhibited by glucose [64]; thus, hyperglycaemia in people with diabetes may affect olfactory function through actions on orexin neurons in the lateral hypothalamus. Melanin concentrating hormone neurons, whose cell bodies are also located in the lateral hypothalamus, are glucose-excited and have been observed to have a potential role in olfactory function.…”
Section: Putative Mechanisms For Olfactory Dysfunction In Diabetesmentioning
confidence: 99%
“…41 Rather than slowly generated, internal feedback signals, such as digested nutrients, allow rapidly measurable sensory information to control food selection, glucose supply for fight-or-flight responses or preparedness for digestion/ absorption. 42 Cephalic phase secretions of the gastrointestinal tract are initiated by activated vagal motor neurons 41 and include both exocrine secretions, such as saliva, gastric acid, and pancreatic enzymes, and endocrine hormones, such as gastrin, insulin, pancreatic polypeptide, and glucagon, among others. 40,43 When a meal is directly administered into the stomach, trespassing sensorial receptors, the early phase of digestion does not occur, corroborating that the sense of sight and smell stimulation is physiologically crucial to release of aforementioned substances and primary organic responses to initiate digestion.…”
Section: Cpr: the Role Of Anticipatory Stimulus On Human Homeostasismentioning
confidence: 99%